Modulation of Angiogenesis for Cancer Prevention: Strategies Based On Antioxidants and Copper Deficiency - Khan, Gazala N.; Merajver, Sofia D. (Current Pharmaceutical Design, 2007)
Although anti- angiogenesis strategies have generated much enthusiasm for therapeutic applications, it is still unknown whether they would be feasible for prevention. The possibility of interfering very early in tumor progression by modulating the cancer angiogenic switch is appealing. In this chapter, we review progress with in vitro and in vivo models that show that anti-angiogenic interventions may be amenable to long- term chemopreventive measures. In particular, some approaches that are nearly ready for major applications are anti-oxidant nutraceuticals and copper deficiency. We use these strategies as paradigms of how to make progress in this difficult but important area of translational research.
Keywords: copper chelation